Pengaruh Kualitas Pelayanan, Harga, dan Inovasi Produk Terhadap Keputusan Pembelian Pada Mie Gacoan Kediri - Adelina, Radica; Listyani, Indah; Kurniawan, Brahma Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine the influence of service quality, price and product innovation on purchasing decisions at Mie Gacoan Kediri which is located at Jl. Urip Sumoharjo No. 88, Kaliombo, District. City, Kediri City. This research uses descriptive quantitative research with incidental sampling techniques with a population of all Mie Gacoan Kediri consumers Jl. Urip Sumoharjo who is unknown and a sample of 100 respondents obtained using the Lemeshow method. The analysis techniques used in this research are instrument tests, classical assumption tests and hypothesis tests in the form of multiple linear regression tests, coefficient of determination, t tests, and F tests. The results of the research show that the service quality variable has a significant positive effect on purchasing decisions partially. , the price variable has no significant positive effect on service quality partially, the product innovation variable has no significant positive effect on purchasing decisions partially, and the service quality, price and product innovation variables have a significant positive effect on purchasing decisions simultaneously.